PENGARUH MOTIVASI KERJA DAN ETOS KERJA TERHADAP PRODUKTIVITAS PEGAWAI PADA PT. BANK SULUTGO KANTOR PUSAT MANADO - Jeane Maramis; Tiara Felia Ondang; Adelaida Joroh (MANAJEMEN ADMINISTRASI BISNIS DAN PEMASARAN, 2023)
In the industrial era 4.0, the Indonesian government is trying to make the development of the Indonesian nation better following the times. The purpose of this study is to determine the Effect of Work Motivation and Work Ethic on Employee Productivity at PT. Bank SulutGo Manado Head Office. This type of research is quantitative research and research methods use Descriptive research methods. Research that took samples from a single population using questionnaires as a data collection tool. The population taken by employees of PT. Bank SulutGo Manado Head Office. The employees in question totaled 78 employees but the sample involved amounted to 65 respondents using the Simple Random Sampling method. The analysis used is Descriptive Statistical Analysis, Total Score, Multiple Linear Regression Analysis and Correlation. The results of the research analysis the value of the correlation coefficient simultaneously r = 0.428 shows that work motivation and work ethic have a strong and significant relationship with increasing employee productivity at PT. Bank SulutGo Manado Head Office. The value of the coefficient of determination shows that the increase in employee productivity, 42.8% is influenced by work motivation and work ethic together, while the remaining 57.2% is influenced by other factors. The results of the analysis show that work motivation and work ethic have a significant influence on increasing employee productivity at PT. Bank SulutGo Manado Head Office. For this reason, work motivation and work ethic need to be considered and maximized by leaders and companies by paying more attention to internal and organizational factors regarding work motivation and work ethic so as to increase employee productivity.